Exodus and its economic and social effects on El-Damazin City in the period between (2020-2022). (Journal of the College of Basic Education, 2024)
The study aimed to identify and define the effects of Exodus on the social and economic aspects particularly in the locality of Damazin. The study followed the historical, descriptive, analytical statistical and the case study approach,and used the observation and the questionnaire as tools for data collection. The data was analyzed by the statistical packages for social sciences (SPSS) program. The study found that there are economic, social and political effects of migration and Exodus on the city of Damazin. The armed conflicts continued to spread throughout the state, which affected health and environment on the study area. The war has social, economic and psychological effects on the community of the city. Trade stopped for a period of time, which affected the city economically. Children who had never witnessed war before, fear entered their hearts, and as a result, some students refrained from studying. Conflicts affected the population, which led to an increase in the displaced. The study recommends the following: Addressing the causes of displacement and asylum by proposing scientific methods that provide the basic requirements of society.